Find the Y-Intercept 6x+2y=12

Math
6x+2y=12
Rewrite in slope-intercept form.
Tap for more steps…
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Subtract 6x from both sides of the equation.
2y=12-6x
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2y=12-6x by 2.
2y2=122+-6×2
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2y2=122+-6×2
Divide y by 1.
y=122+-6×2
y=122+-6×2
Simplify 122+-6×2.
Tap for more steps…
Simplify each term.
Tap for more steps…
Divide 12 by 2.
y=6+-6×2
Cancel the common factor of -6 and 2.
Tap for more steps…
Factor 2 out of -6x.
y=6+2(-3x)2
Cancel the common factors.
Tap for more steps…
Factor 2 out of 2.
y=6+2(-3x)2(1)
Cancel the common factor.
y=6+2(-3x)2⋅1
Rewrite the expression.
y=6+-3×1
Divide -3x by 1.
y=6-3x
y=6-3x
y=6-3x
y=6-3x
Reorder 6 and -3x.
y=-3x+6
y=-3x+6
y=-3x+6
y=-3x+6
Using the slope-intercept form, the y-intercept is 6.
b=6
Find the Y-Intercept 6x+2y=12

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top